To start or not to start? An exploratory study of work meaningfulness among start-up co-founders - Deniz Dirik; Burak Özdoğan (Frontiers in Psychology)
This study explores startup co-founders’ perceptions of meaningful work experiences in the dynamic and uncertain context of entrepreneurship. While entrepreneurial research has extensively examined firm-level outcomes such as performance and growth, the subjective experiences of entrepreneurs have remained relatively underexplored especially in an emerging country context. This study addresses meaningful work experiences of 12 startup co-founders from Turkiye by employing a qualitative research design and using in-depth interviews. Drawing on Self-Determination Theory (SDT) and the Job Characteristics Model (JCM), this research identifies key dimensions of meaningful work, including significance, autonomy, identity, challenge and resilience, recognition and support, and work-life balance. Our findings suggest that the complex interplay of intrinsic motivation and external validation contributes significantly to perceived entrepreneurial well-being and resilience. We present a three-dimensional model of perceived meaningfulness with professional, psychological, and societal aspects for meaningfulness experiences. We extend existing literature by demonstrating how startup ventures offer fertile ground for psychological fulfillment, not merely through financial success but through personal growth and societal impact.